2018
DOI: 10.1038/s41375-018-0276-9
|View full text |Cite
|
Sign up to set email alerts
|

Updated results from the phase 3 HELIOS study of ibrutinib, bendamustine, and rituximab in relapsed chronic lymphocytic leukemia/small lymphocytic lymphoma

Abstract: We report follow-up results from the randomized, placebo-controlled, phase 3 HELIOS trial of ibrutinib+bendamustine and rituximab (BR) for previously treated chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) without deletion 17p. Overall, 578 patients were randomized 1:1 to either ibrutinib (420 mg daily) or placebo, in combination with 6 cycles of BR, followed by ibrutinib or placebo alone. Median follow-up was 34.8 months (range: 0.1–45.8). Investigator-assessed median progression-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 23 publications
5
97
1
5
Order By: Relevance
“…The CR/CRi rates have increased over time with ibrutinib treatment, approaching a plateau beyond 3.5 years (9% and 11% with median 44 and 64 months of follow‐up, respectively). This is consistent with deepening of response with continuous ibrutinib therapy for responding patients and is similar to the improved responses observed over time with longer follow‐up in patients with relapsed/refractory CLL in the HELIOS study and in the phase 2 PCYC‐1102/1103 study . Notably, the proportion of patients who reported clinically meaningful improvement in FACIT‐F score was greater with ibrutinib than ofatumumab, and the improvement was maintained over time.…”
Section: Discussionsupporting
confidence: 81%
“…The CR/CRi rates have increased over time with ibrutinib treatment, approaching a plateau beyond 3.5 years (9% and 11% with median 44 and 64 months of follow‐up, respectively). This is consistent with deepening of response with continuous ibrutinib therapy for responding patients and is similar to the improved responses observed over time with longer follow‐up in patients with relapsed/refractory CLL in the HELIOS study and in the phase 2 PCYC‐1102/1103 study . Notably, the proportion of patients who reported clinically meaningful improvement in FACIT‐F score was greater with ibrutinib than ofatumumab, and the improvement was maintained over time.…”
Section: Discussionsupporting
confidence: 81%
“…20 Its evidence as second-line treatment is even more sparse, as the pivotal clinical study was a small single-arm phase 2 trial 21 and phase 3 studies have shown a poor effect of BR at relapse compared to novel agents. [22][23][24] Although a recent observational study concluded that BR is an effective salvage at first relapse, 25…”
Section: Treatment Regimens and Overall Survivalmentioning
confidence: 99%
“…CLL kezelé sében az elmúlt években a másik rendkívül hatékony elsőnek választandó szer a Bruton-tirozin-kináz-(BTK-) gátló ibrutinib. Az ibrutinibkezelés hatékonyságát több klinikai vizsgálat is igazolta [19,20], azonban BTK-gátlás hatására az esetek többségében nem volt elérhető uMRD-szint [21]. Továbbá egy másik klinikai vizsgálat megmutatta, hogy nincs jelentős különbség az uMRD-és a dMRD-státuszú ibrutinibbel kezelt betegek túlélése között [22].…”
Section: Mrd Meghatározása a Klinikai Vizsgálatok Tükrébenunclassified